Super-Multiple Deletion Analysis of Type III Effectors in Ralstonia solanacearum OE1-1 for Full Virulence Toward Host Plants - Lei, Ni; Chen, Li; Kiba, Akinori; Hikichi, Yasufumi; Zhang, Yong; Ohnishi, Kouhei (Frontiers in Microbiology, 2020)
Ralstonia solanacearum species complex (RSSC) posses extremely abundant type III effectors (T3Es) that are injected into hosts cell by a syringe-like type III secretion system (T3SS) to subvert host defense initiated by innate immunity. More than 100T3Es are predicated among the RSSC with an average of about 70 T3Es in each strain, and the 32 core T3Es are conserved in the RSSC. Here, we genetically characterized contribution of T3Es to virulence of a Japanese strain OE1-1 on host plants. All the T3Es members of AWR family contributed together slightly to virulence, but not those of each family of GALA, HLK, and SKWP. Mutant OE1-1D21E (In Pseudomonas syrinagae, they used the same expression, DC3000D29E, with deletion of all 21 T3Es members of four families) exhibited slightly impaired virulence, while mutant OE1-1D36E (deleting all the T3Es of above four families and core T3Es) exhibited substantially impaired virulence. Mutant OE1-1D42E (deleting all the T3Es of above four families, the core and additional core T3Es) failed to cause any disease on tobacco plants with leaf infiltration but remained faint virulence with petiole inoculation. The proliferation of mutant OE1-1D42E in tobacco stems was substantially impaired with about three orders of magnitude less than that of OE1-1, but no impact in tobacco leaves if directly infiltrated into tobacco leaves.On the contrary, mutant OE1-1D42E completely lost virulence on eggplants with root-cutting inoculation, but remained faint virulence with leaf infiltration. The proliferation of OE1-1D42E mutant both in eggplant leaves and stems was substantially impaired. Intriguingly, the mutant OE1-1D42E still caused necrotic lesions in tobacco and eggplant leaves, indicating that some other T3Es besides the core and additional core T3Es are involved in the expansion of necrotic lesions in the leaves. All taken together, we here demonstrated that all the core and additional core T3Es are essential for virulence of OE1-1 and provided a T3Es-free strain that enables primary functional studies of individual T3Es in host cells.